Semantic Grid: Scientific Issues, Infrastructure, and Methodology. - Hai Zhuge (Communications of the ACM, 2005)
This article reports that database theory and systems, a seminal development of information management, has profoundly affected computer applications for nearly 40 years. The Internet is a brilliant innovation, with unprecedented social and economic influence, but the lack of a theoretical foundation has limited its full potential. The Internet and the Web share four characteristics--rapid expansion of versatile resources and users, micro structured and macro-scale-free resource organization, inequality of information reputation, and human understandable, not machine-understandable, semantics. The Semantic Grid is an Internet centered interconnection environment that can effectively organize, share, cluster, fuse, and manage globally distributed versatile resources based on the interconnection semantics. Interconnection semantics is the study of the semantics in the interconnection environment for supporting intelligent applications by meaningfully interconnecting resources in semantic spaces where machines and humans can understand each other. Different from the semantics of natural and programming languages, interconnection semantics concerns.